THE IMPACT OF THE HOSTAGE-TAKING OF CAPTAIN PHILIP MEHRTENS ON INDONESIA–NEW ZEALAND BILATERAL RELATIONS - Sinaga, Melpayanty; Amenes, Apriani Anastasia (Department of International Relations Universitas Satya Negara Indonesia, 2026)
The objective of this research is to examine the impact of the bilateral relationship between Indonesia and New Zealand (NZ) from 2023 to the present. The selection of this timeframe is due to a hostage-taking incident carried out by Captain Philip Mehrtens, an NZ citizen working as a pilot for Susi Air in Nduga Regency, Papua Pegunungan Province. This hostage-taking was carried out by the West Papua National Liberation Army (TPNPB) under the leadership of Sebby Sambom. The research method employed is qualitative, utilizing a case study design, and incorporates conflict theory and the concept of bilateral cooperation. The study’s finding is that the bilateral relationship between Indonesia and NZ is characterized by a high degree of resilience, which does not impede cooperation in economic, energy, education, and security domains. These factors, caused by the recognition of the government of NZ for Indonesia’s sovereignty over the Papua region, mutual trust between Indonesia and NZ since 1958, and the release of hostage using a non-military approach involving negotiations with local actors such as religious leaders, customary leaders, and local government.